2005
DOI: 10.1007/s10340-004-0078-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transgenic cry1Ab rice pollen on fitness of Propylea japonica (Thunberg)

Abstract: The transgenic rice lines Kemingdao 1 (KMD1) and Kemingdao 2 (KMD2) contain a synthetic cry1Ab gene derived from Bacillus thuringiensis Berliner and are highly resistant to rice stem borers and foliage-feeding lepidopterans. Propylea japonica (Coleoptera: Coccinellidae) is an important predator of rice insect pests; it also uses rice pollen as a food source under natural conditions. In the present study, the effects of KMD1 and KMD2 pollen expressing Cry1Ab protein on the fitness of P. japonica were assessed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Some predatory ladybird beetles were found to feed directly on prey's host plant tissues and their development could be affected (Bai et al 2005;Moser et al 2008;Lundgren et al 2009). Therefore, some biological characteristic differences of H. variegata fed on aphids from different host plants might be caused directly or indirectly (prey-mediated) by host plants because the aphids and plant leaves were provided together to the beetles.…”
Section: Life Table Parametersmentioning
confidence: 98%
“…Some predatory ladybird beetles were found to feed directly on prey's host plant tissues and their development could be affected (Bai et al 2005;Moser et al 2008;Lundgren et al 2009). Therefore, some biological characteristic differences of H. variegata fed on aphids from different host plants might be caused directly or indirectly (prey-mediated) by host plants because the aphids and plant leaves were provided together to the beetles.…”
Section: Life Table Parametersmentioning
confidence: 98%
“…Although they state ''datadriven reading of the quantitative data…provided a more accurate picture of the literature…than (the reviews) by O'Callaghan et al (2005) and Romeis et al (2006)'', they provide no evidence to support this statement. They cite Bai et al (2005) as an example of the need to use their analytical methods to tease out negative results, but neglect to note that in the Bai et al (2005) study total larval development and survivorship of Propylea japonica (Thunberg) (Coleoptera: Coccinellidae) were unaffected by exposure to Cry proteins. These are the quantities that ultimately affect population growth and are of primary importance as measurement endpoints in risk assessment studies (including those conducted for pesticide assessment; Romeis et al 2008).…”
Section: Data Selection and Analysesmentioning
confidence: 99%
“…These are the quantities that ultimately affect population growth and are of primary importance as measurement endpoints in risk assessment studies (including those conducted for pesticide assessment; Romeis et al 2008). For this reason, Bai et al (2005) correctly concluded ''Bt rice pollen had no negative impacts on P. japonica fitness…''. Lövei et al (2009) also fail to justify the many other instances of nonindependence in their data set where multiple, correlated life history and behavioral traits were measured on the same cohort of subject organisms.…”
Section: Data Selection and Analysesmentioning
confidence: 99%
“…Direct exposure of Cheilomenes sexmaculatus larvae to Cry1Ab and Cry1Ac toxins resulted in reduced larval survival and adult emergene as compared to the controls, however, there were no adverse effects of Cry1A toxins on coccinellid beetle when the larvae were reared on Aphis craccivora Koch fed on Cry1A in the artificial diet (Dhillon and Sharma 2009). Minimal or no impacts of Bt plants or Cry1A toxins to predatory beetles were also reported (Bai et al 2005;Ferry et al 2006). Bt maize had no negative effects on survival of the predator Stethorus punctillum, or on the developmental time through to adulthood, and no subsequent effects on ladybird fecundity were observed (Á lvarez-Alfageme et al 2008(Á lvarez-Alfageme et al , 2009).…”
Section: Discussionmentioning
confidence: 85%